1992
DOI: 10.1111/j.1365-2230.1992.tb00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Selenium plasma levels in psoriasis

Abstract: Little is known about factors that may have modulating effects on inflammatory diseases such as psoriasis. Recently it has been proposed that trace elements like selenium may play an active role. Selenium concentrations were determined in plasma and in whole blood from 64 patients with psoriasis. Values were compared with those of matched controls: no significant reduction was observed in contrast with previous reports of reduced selenium levels in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…GPX4 knockout has been proved to induce ferroptosis-related necroinflammation in skin tissue (130)(131)(132). For the reason that ceramide analogs are testified to be an effective therapeutic in animal experiments, it is speculated that upregulating GPX4 might significantly relieve skin from ferroptosis-induced necroinflammatory injury (96,97).…”
Section: Integumentary System Diseasesmentioning
confidence: 99%
“…GPX4 knockout has been proved to induce ferroptosis-related necroinflammation in skin tissue (130)(131)(132). For the reason that ceramide analogs are testified to be an effective therapeutic in animal experiments, it is speculated that upregulating GPX4 might significantly relieve skin from ferroptosis-induced necroinflammatory injury (96,97).…”
Section: Integumentary System Diseasesmentioning
confidence: 99%
“…Defects in the absorption of selenomethionine from the gut of psoriatic and atopic dermatitis patients did not differ significantly from controls’ [8]. Other studies showed no difference in selenium levels in patients with psoriasis compared with normal controls [9]. In short, the connection between selenium and psoriasis is unclear, with poor understanding of the absorption, handling of inorganic vs organic selenium, and transport of active selenium moieties to the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Serum Se, and (better) whole blood Se levels reflect the current Se status of the individual, and median levels obtained within a region indicate a general level of supply. The difference between Se concentrations in human plasma and whole blood is about 30 % [135]. Apart from local feeding habits, blood plasma and serum levels of coastal populations are generally higher than from inside the continents, thus, seafood is a very significant source of Se (Table 3).…”
Section: Occurrence In Food For Human Nutritionmentioning
confidence: 99%